An overview on sequentially g-quotient maps. (2022) - Vijayashanthi, P.; Verma, Kirti; Dixit, Sonal; Pandey, Sudeep Kumar; Sathya, E.; Arunkumar, M.
Abstract: In this paper, we propose inverse image characterizations of sequentially g-continuous mappings. We introduce the concept of a sequentially g-quotient map and discuss some of the characteristics of sequentially g-quotient mappings. The most common uses of mappings are presented as functional characterizations of g-sequential spaces as domains and ranges of certain mappings. There is also some discussion of examples to illustrate the research methodologies.